Distress, Dissent and Alienation: Hamilton Workers in the Great Depression - Archibald, W. (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1992)
Contrary to most accounts of Canadian workers' responses to the Great Depression of the 1930s, this article portrays the majority of Hamilton workers as neither severely distressed nor especially prone to dissent. Much of the relative absence of dissent can be attributed to workers' powerlessness in very poor market conditions, but workers' quiescence should not be seen simply as a temporary, class-conscious strategy. Rather, many, perhaps most, workers either regarded dissent as illegitimate to begin with, or/and lowered their aspirations for secure and self-controlled work in the prevailing labour market and other conditions. In other words, they became psychically "alienated". These findings have important implications for most theorizing on these issues, which implicitly employs a "frustration-aggression" model; for popular conceptions of workers as highly class-conscious and epically heroic; and for organizing workers during most economic crises.